2018
DOI: 10.1111/tan.13398
|View full text |Cite
|
Sign up to set email alerts
|

The prevalent Boxer MHC class Ia allotype dog leukocyte antigen (DLA)‐88*034:01 preferentially binds nonamer peptides with a defined motif

Abstract: Development of effective immunotherapy for chemoresistant malignancies can be advanced by studies in spontaneous cancer models, such as the dog. A crucial first step, T‐cell epitope discovery, can be assisted by determination of binding motifs of common dog leukocyte antigen (DLA) class Ia allotypes. Boxers are popular, inbred dogs with increased risks of relevant target cancers and restricted MHC diversity. We sought to identify the motif of DLA‐88*034:01, a breed‐dominant allotype, to assist peptide predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Why no X‐linked CTAs were recovered here is unknown, but may reflect the insensitivity of the mass spectrometric approach or peculiarities of the DH82 cell line (note that peptides from nine non‐CTA genes residing on the X chromosome were recovered in our experiments, ruling out whole chromosome loss). Interestingly, Chen et al observed MAGE expression via immunohistochemistry in histiocytic proliferative disease biopsy specimens, but to date we have not identified MAGE peptides in DH82, even when a different DLA‐88 allele, *034:01, has been immunoprecipitated (in three independent experiments) . An additional explanation for this dearth is that the canine genome appears to lack definitive orthologs of many of the human X‐linked CTAs, which are evolutionarily young genes, with many family members arising after the divergence of Laurasiatherian mammals …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Why no X‐linked CTAs were recovered here is unknown, but may reflect the insensitivity of the mass spectrometric approach or peculiarities of the DH82 cell line (note that peptides from nine non‐CTA genes residing on the X chromosome were recovered in our experiments, ruling out whole chromosome loss). Interestingly, Chen et al observed MAGE expression via immunohistochemistry in histiocytic proliferative disease biopsy specimens, but to date we have not identified MAGE peptides in DH82, even when a different DLA‐88 allele, *034:01, has been immunoprecipitated (in three independent experiments) . An additional explanation for this dearth is that the canine genome appears to lack definitive orthologs of many of the human X‐linked CTAs, which are evolutionarily young genes, with many family members arising after the divergence of Laurasiatherian mammals …”
Section: Discussionmentioning
confidence: 69%
“…human CTAs such as MAGE-A3 and NY-ESO-1 ( 64 An additional explanation for this dearth is that the canine genome appears to lack definitive orthologs of many of the human X-linked CTAs, which are evolutionarily young genes, with many family members arising after the divergence of Laurasiatherian mammals. 65,66 Expression of some CTAs in transformed cells may represent an epiphenomenon of altered genomic methylation or acquisition of stem-like properties, but in general, CTAs are thought to contribute to oncogenesis, 67 presumably to a degree sufficient to offset the increased immunogenicity and susceptibility to immunoediting (expression of CTAs can be associated with CD8+ T-cell signatures in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, progress toward studying canine CD8+ T cells has been made. The binding motifs of three MHC class I allomorphs, DLA‐88*501:01, 88*508:01, and 88*034:01, have been reported 15‐17 . Their presentation of diverse peptides supports DLA‐88 as a classical locus.…”
Section: Figurementioning
confidence: 97%
“…We recently analyzed the peptidome of DLA‐88*034:01 by liquid chromotography‐tandem mass spectrometry (LC‐MS/MS), and deduced the putative binding motif by consensus analysis 17 . The intent was to provide accurate predictions of neoepitopes in the tumor mutanomes of Boxers carrying the allele.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation